2019
DOI: 10.1002/ccd.28166
|View full text |Cite
|
Sign up to set email alerts
|

Short‐ and long‐term results with a percutaneous treatment in critical hand ischaemia

Abstract: Background The aim of this prospective registry was to determine the feasibility, safety, and outcomes of percutaneous transluminal angioplasty and thrombolysis in the treatment of critical hand ischemia (CHI). Methods One‐hundred one patients (aged 60.6 ± 15.3 years) were treated for CHI between 2012 and 2016 in three cardiovascular centers. Anatomically, the upper arm was divided into three segments (I‐subclavian, II‐brachial, and III‐forearm). We examined the rates of technical and clinical success, major a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(26 citation statements)
references
References 12 publications
0
26
0
Order By: Relevance
“…Percutaneous revascularization is commonly performed for limb salvage in lower extremity atherosclerotic disease and has been shown to be safe in small cohorts of patients with other forms of critical limb ischemia (CLI). 6 , 7 Patients with lower extremity CLI of any cause often present with chronic occlusion of small-caliber (≤3-mm diameter) arteries, which can be successfully revascularized using contemporary endovascular techniques in most cases. We hypothesized that this approach could be used to treat refractory upper extremity digital ischemia in our patient.…”
Section: Discussionmentioning
confidence: 99%
“…Percutaneous revascularization is commonly performed for limb salvage in lower extremity atherosclerotic disease and has been shown to be safe in small cohorts of patients with other forms of critical limb ischemia (CLI). 6 , 7 Patients with lower extremity CLI of any cause often present with chronic occlusion of small-caliber (≤3-mm diameter) arteries, which can be successfully revascularized using contemporary endovascular techniques in most cases. We hypothesized that this approach could be used to treat refractory upper extremity digital ischemia in our patient.…”
Section: Discussionmentioning
confidence: 99%
“…This report describes a rare case of technically and clinically successful revascularization in a BTE lesion with total occlusion from the distal RA and UA to the palmar artery in a patient with SSc. Endovascular therapy for BTE lesions in patients with CHI associated with atherosclerosis has been reported as a feasible treatment option for revascularization 5-8 ; therefore, endovascular intervention for BTE lesions in patients with CHI associated with SSc might be considered as a treatment option. An antegrade approach should be attempted first in BTE interventions, but a retrograde approach via the palmar arch may be useful as an alternative if this attempt fails.…”
Section: Discussionmentioning
confidence: 99%
“…Complications and limb loss data are presented in Table 4 13 Although the Ruzsa et al study reported 42/101 cumulative major adverse event rate at 3 years, the data includes outcomes for both ATE and BTE revascularization. 9 Nearly 20% of patients required an amputation, and most (96%) were minor (either distal phalanges or digits). Only 2 patients required above-wrist amputations.…”
Section: Complications and Mortalitymentioning
confidence: 99%
“… 4 , 5 There is usually a diffuse involvement of the BTE vessels, including the ulnar artery, radial artery, palmar arch, and digital vessels, with seldom isolated involvement of the interosseous artery. 4 - 10 Distal calcific arteriosclerosis plays a pivotal role in the pathophysiology of hand ischemia, particularly in hemodialysis patients. 5…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation